Implementasi Pembiasaan Ibadah Harian dalam Pembentukan Kesadaran Spiritual Siswa di Maahad Tahfidz Vokasional Aman Bistari Malaysia - Nikmatul Maula, Liya; Djamal, M.; Hidayah, Nurul (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the implementation of daily worship habits in shaping students' spiritual awareness at Maahad Tahfidz Vokasional Aman Bistari, Malaysia. Using a qualitative case study approach supported by descriptive quantitative data, it is categorized as a mixed-methods study. Data were obtained through interviews, observations, questionnaires, and documentation. The results of this study indicate that daily worship practices, such as congregational prayer, dhikr, tilawah, and qiyamullail, are carried out in a structured and consistent manner, thereby not only forming religious routines but also fostering students' spiritual awareness in cognitive, affective, and behavioral aspects. This awareness is reflected in increased discipline, sincerity, patience, and social awareness, as well as a shift in students' motivation from compliance with rules to personal spiritual needs. The main supporting factors include teacher role modeling, supervision, and a conducive religious environment. These findings show that the success of worship habits depends not only on the frequency of activities but also on the quality of spiritual reflection that accompanies them. Thus, daily worship habits have proven to be effective as a pedagogical strategy in internalizing spiritual values and shaping students' character, as well as being a relevant model of Islamic education for facing the challenges of modernization and a reference for similar educational institutions.